(untitled) (Revista Venezolana de Salud Pública, 2018)
The aim of the present study is to determine the epidemiological characteristics of mortality related to in Lara State during the period 2000-2010; through a retrospective longitudinal descriptive investigation. We checked the mortality information of Regional Epidemiology of the MPPS. We studied 823 deaths corresponding to the code C53 of ICD-10. The deaths by cervical cancer represented 1% of the total amount of deaths by all the causes during the studied period. 98.7% was due to not specified uterine neck malignant tumor; the 65 years group and even more has high risk of dying because of this cause with a rate of 59,34 per 105 hab., the 55-64 years group was the next (32,59 per 105 hab.). The areas with high mortality risk are Iribarren and Urdaneta municipalities (rate of 100,22 per 105 hab. and 112,25 per 105 hab. respectively). 36,8 % of deaths which took place at Iribarren municipality belong to the Juan de Villegas area. The biggest risk of dying occurred during 2005 and 2008 (rates of 12.26 per 105 hab. and 10.02 per 105 hab. respectively). We demonstrate due to this fact 2.690 PYLL get lost. This study will be important to other investigations; it is going to contribute information to the sector health to facilitate the capture of decisions in the control and prevention of the cervical cancer.